Preparedness Lessons from Modern Disasters and Wars - Dara, Saqib I. (Crit Care Clin, 2009)
Disasters come in all shapes and forms, and in varying magnitudes and intensities. Nevertheless, they offer many of the same lessons for critical care practitioners and responders. Among these, the most important is that well thought out risk assessment and focused planning are vital. Such assessment and planning require proper training for providers to recognize and treat injury from disaster, while maintaining safety for themselves and others. This article discusses risk assessment and planning in the context of disasters. The article also elaborates on the progress toward the creation of portable, credible, sustainable, and sophisticated critical care outside the walls of an intensive care unit. Finally, the article summarizes yields from military-civilian collaboration in disaster planning and response.